2021
DOI: 10.3390/genes12081106
|View full text |Cite
|
Sign up to set email alerts
|

Plants’ Epigenetic Mechanisms and Abiotic Stress

Abstract: Plants are sessile organisms that need to adapt to constantly changing environmental conditions. Unpredictable climate change places plants under a variety of abiotic stresses. Studying the regulation of stress-responsive genes can help to understand plants’ ability to adapt to fluctuating environmental conditions. Changes in epigenetic marks such as histone modifications and DNA methylation are known to regulate gene expression by their dynamic variation in response to stimuli. This can then affect their phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 128 publications
(176 reference statements)
0
66
0
2
Order By: Relevance
“…Throughout their evolutionary history, plants have adapted to widely varied and sometimes very stressful environments. The efficiency of their adaptation to environmental stresses (such as extreme temperature, high salinity, and hypoxia), not only depends on the presence of stress response genes, but it also relies on how the expression of those genes is controlled [1]. When plants encounter environmental pressure, the expression of related genes will change accordingly, in order to help plants to overcome and survive the stress, which can especially be important for long living plants that have to cope with different kind of undesirable conditions during their long lifespan [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout their evolutionary history, plants have adapted to widely varied and sometimes very stressful environments. The efficiency of their adaptation to environmental stresses (such as extreme temperature, high salinity, and hypoxia), not only depends on the presence of stress response genes, but it also relies on how the expression of those genes is controlled [1]. When plants encounter environmental pressure, the expression of related genes will change accordingly, in order to help plants to overcome and survive the stress, which can especially be important for long living plants that have to cope with different kind of undesirable conditions during their long lifespan [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This supports the hypothesis that DNA methylation regulates abiotic gene expression. Drought in several plant species leads to substantial remodelling of DNA methylation, which allows plants to respond more effectively to recurring stress and prepares offspring for future stress responses [272]. However, in this case, modifying DNA methylation still seems to be essential to regulate neighbouring gene expression [273].…”
Section: Abiotic Stressmentioning
confidence: 99%
“…In addition to histone modifications and DNA methylation, ATP-dependent chromatin reorganization modulates the DNA accessibility for transcription factors and RNA polymerase II, and therefore regulates the transcription of the genes within the chromatin structure [ 61 , 62 , 63 ]. This dynamic change of DNA accessibility influences many processes in plants, including developmental events, such as flowering time and senescence, as well as the response to stresses and environmental changes [ 64 , 65 ]. Studies have shown that changes in the chromatin structure during senescence by chromatin-remodeler enzymes play an important role in controlling leaf senescence [ 17 ].…”
Section: Atp-dependent Chromatin Remodeling and Senescencementioning
confidence: 99%